Hereditary diffuse gastric cancer: updated clinical guidelines with an emphasis on germline CDH1 mutation carriers. Issue 6 (15th May 2015) - van der Post, Rachel S; Vogelaar, Ingrid P; Carneiro, Fátima; Guilford, Parry; Huntsman, David; Hoogerbrugge, Nicoline; Caldas, Carlos; Chelcun Schreiber, Karen E; Hardwick, Richard H; Ausems, Margreet G E M; Bardram, Linda; Benusiglio, Patrick R; et al.
Abstract : Germline CDH1 mutations confer a high lifetime risk of developing diffuse gastric (DGC) and lobular breast cancer (LBC). A multidisciplinary workshop was organised to discuss genetic testing, surgery, surveillance strategies, pathology reporting and the patient's perspective on multiple aspects, including diet post gastrectomy. The updated guidelines include revised CDH1 testing criteria (taking into account first-degree and second-degree relatives): (1) families with two or more patients with gastric cancer at any age, one confirmed DGC; (2) individuals with DGC before the age of 40 and (3) families with diagnoses of both DGC and LBC (one diagnosis before the age of 50). Additionally, CDH1 testing could be considered in patients with bilateral or familial LBC before the age of 50, patients with DGC and cleft lip/palate, and those with precursor lesions for signet ring cell carcinoma. Given the high mortality associated with invasive disease, prophylactic total gastrectomy at a centre of expertise is advised for individuals with pathogenic CDH1 mutations. Breast cancer surveillance with annual breast MRI starting at age 30 for women with a CDH1 mutation is recommended. Standardised endoscopic surveillance in experienced centres is recommended for those opting not to have gastrectomy at the current time, those with CDH1 variants of uncertain significance and those that fulfil hereditary DGC criteria without germline CDH1 mutations. Expert histopathological confirmation of (early) signet ring cell carcinoma is recommended. The impact of gastrectomy and mastectomy should not be underestimated; these can have severe consequences on a psychological, physiological and metabolic level. Nutritional problems should be carefully monitored.